HUMAN RESOURCE STRATEGY: ENHANCING ORGANIZATIONAL PERFORMANCE THROUGH EFFECTIVE HRM - Maria Batool; Muhammad Nadim; Dr. Ahmed Farhan Saeed; Fazli Wadood; Muneera Quresh; Dr. Maja Pucelj (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
In light of today's rapidly changing economic climate, this study investigates the role that HR strategy plays in raising the bar for corporate success. Using a literature synthesis approach, this research intends to illuminate the critical variables that lead to organizational performance by analyzing and comparing a variety of HRM theories and strategic HR practices. This study's overarching research topic investigates how strategic HRM improves organizational effectiveness by fostering a productive work environment, attracting and retaining the best employees, and boosting morale and productivity. The study takes a qualitative tack by relying heavily on a review of the existing literature. In order to maximize human capital for competitive advantage and sustainable growth, the results show how important strategic HRM is. The effects of strategic HRM on managing employees and improving productivity are discussed. This paper concludes that long-term success can be driven by a combination of positive work culture and HR policies that are aligned with company goals.